1994
DOI: 10.1111/j.1432-1033.1994.tb18809.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the ɛ‐aminohexanoic acid complex of human plasminogen kringle 1

Abstract: The solution structure of the human plasminogen kringle 1 domain complexed to the antifibrinolytic drug 6-aminohexanoic acid (epsilon Ahx) was obtained on the basis of 1H-NMR spectroscopic data and dynamical simulated annealing calculations. Two sets of structures were derived starting from (a) random coil conformations and (b) the (mutated) crystallographic structure of the homologous prothrombin kringle 1. The two sets display essentially the same backbone folding (pairwise root-mean-square deviation, 0.15 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 57 publications
(62 reference statements)
3
50
1
Order By: Relevance
“…Thus, it is suggested that the hairpin turn connecting the two antiparallel strands differs among the kringles with a type I turn spanning residues 67-70 in the case of PgdK4. Structure calculations [41] show a similar backbone conformation for PgdK1 in this region (Fig. 7H).…”
Section: Comparison Of /%Sheets and Hairpin Turns In Kringlesmentioning
confidence: 76%
See 4 more Smart Citations
“…Thus, it is suggested that the hairpin turn connecting the two antiparallel strands differs among the kringles with a type I turn spanning residues 67-70 in the case of PgdK4. Structure calculations [41] show a similar backbone conformation for PgdK1 in this region (Fig. 7H).…”
Section: Comparison Of /%Sheets and Hairpin Turns In Kringlesmentioning
confidence: 76%
“…A bifurcated hydrogen bond involving the Thrl6 carbonyl (Fig. 6 A) is suggested by complete structure calculations [41]. The stretch Lys24-Trp25-Ser26-Ser27 delineates a type I or 11' turn [62].…”
Section: Secondary Structurementioning
confidence: 99%
See 3 more Smart Citations